Lump Solutions to the (3+1)-Dimensional Generalized B-Type Kadomtsev-Petviashvili Equation - Xifang Cao (Advances in Mathematical Physics)
This paper is devoted to the study of lump solutions to the (3+1)-dimensional generalized B-type Kadomtsev-Petviashvili equation. First we use a direct method to construct a class of exact solutions which contain six arbitrary real constants. Then we use these solutions to generate lump solutions with four real parameters. We also determine the amplitude and velocity of these lumps.